'Powerful' human rights education's curriculum problems. Issue 4 (3rd July 2020) - Sen, Abdulkerim
ABSTRACT: In an effort to support the curricular institutionalisation of human rights education (HRE) as a school subject, Walter Parker has proposed a curriculum model based on the powerful knowledge (PK) thesis developed by a group of social realist educators. This article aims to contribute to this worthwhile endeavour to develop a consensual HRE curriculum model by identifying four issues with Parker's proposition. While Parker argues the prevalence of constructivism impeded the development of an HRE, the author argues that the negative implications of constructivism for traditional subjects are not true for HRE. After expanding on the other two issues, Sen notes empirical evidence from an HRE textbook, in use in Turkey, to support his fourth point that what is key to a powerful HRE is political support. The article ends with a call to the HRE community to contemplate political impediments that risk making HRE an ineffective enterprise at schools.